2013
DOI: 10.1096/fj.13-231084
|View full text |Cite
|
Sign up to set email alerts
|

Nonaggressive and adapted social cognition is controlled by the interplay between noradrenergic and nicotinic receptor mechanisms in the prefrontal cortex

Abstract: Social animals establish flexible behaviors and integrated decision-making processes to adapt to social environments. Such behaviors are impaired in all major neuropsychiatric disorders and depend on the prefrontal cortex (PFC). We previously showed that nicotinic acetylcholine receptors (nAChRs) and norepinephrine (NE) in the PFC are necessary for mice to show adapted social cognition. Here, we investigated how the cholinergic and NE systems converge within the PFC to modulate social behavior. We used a socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 81 publications
6
29
0
Order By: Relevance
“…For instance, aggressive attitude and enhanced ambulation and rearing frequencies were attributed to elevated dopamine and reduced serotonin levels in brain (Abílio et al, 1999;Van Erp and Miczek, 2000). Moreover, the balance between nor-epinephrine and cholinergic systems may influence social behaviors and aggression (Zarrindast et al, 2012;Coura et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For instance, aggressive attitude and enhanced ambulation and rearing frequencies were attributed to elevated dopamine and reduced serotonin levels in brain (Abílio et al, 1999;Van Erp and Miczek, 2000). Moreover, the balance between nor-epinephrine and cholinergic systems may influence social behaviors and aggression (Zarrindast et al, 2012;Coura et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A recent study investigating how social behavior is regulated by cholinergic and norepinephrine transmission in the prefrontal cortex (PFC) used β2 subunit knockout mice (β2 −/− ) in a social interaction task, which included a measure of aggressivity (Coura et al, 2013). At baseline, β2 −/− mice exhibit increased levels of norepinephrine, dopamine, serotonin, and acetylcholine within the prelimbic region of the PFC, yet display similar levels of aggression compared to control mice both before and after global norepinephrine depletion.…”
Section: Introductionmentioning
confidence: 99%
“…At baseline, β2 −/− mice exhibit increased levels of norepinephrine, dopamine, serotonin, and acetylcholine within the prelimbic region of the PFC, yet display similar levels of aggression compared to control mice both before and after global norepinephrine depletion. Specific norepinephrine depletion in the prelimbic region of the PFC markedly increased aggression in control, but not β2 −/− mice, a finding that suggests aggression was modulated by the balance of monoamines and acetylcholine in the prelimbic cortex, and requires functional β2 nAChRs (Coura et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Particularly, in a social interaction task (SIT) designed to emphasize free social interaction, with potential risk of aggressiveness by an unknown conspecific (Cambon et al, 2010), we showed that β2 −/− mice exhibited higher level of dominance and lower level of flexibility, in relation with their prefrontal hyper-monoaminergia (Coura et al, 2013). In addition, using a dedicated software to pinpoint social decisions by the probabilistic analysis of more than 20 social sequences within the normal social repertoire (De Chaumont et al, 2012), we showed that depleting the noradrenergic prefrontal innervation in normal mice shrinks the decision tree in this task, with lesioned mice making more rigid and non-adaptive decisions leading to aggressiveness (Coura et al, 2013). A deeper analysis of β2 −/− mice' behavior (De Chaumont et al, 2012) was performed by the off line dissection of their behavioral repertoire during the SIT.…”
Section: Introductionmentioning
confidence: 99%
“…It was therefore unkown whether β2 −/− mice were more attracted by the social partner because social rewards were more interesting to them, or if they replied more strongly to a social partner that they may perceive as a putative threat. The latter point could be linked to their major increase in dominance behaviors (Coura et al, 2013), and their proneness to exhibit rigid follow behaviors (De Chaumont et al, 2012). …”
Section: Introductionmentioning
confidence: 99%